Comparing difficulty between a problem of estimation and one of conditional probability - Attorresi, Horacio Félix; García Díaz, Alcira Myriam; Pralong, Héctor Omar (Journal of Psychology, 2023)
This work evaluated the difficulty posed by probability problems in two randomness scenarios with different characteristics. In the first one, proportions were compared and probability was estimated in two samples of different sizes, while the second one presented a conditional probability problem. The responses were categorized on the basis of cognitive understanding and potential bias, such as the representativeness heuristic. Results showed 28% of successful responses and 42% of responses involving the heuristic in the first problem, and no correct responses to the conditional probability problem. The sample was selected on accessibility grounds, and the items were administered to two groups of students recently admitted to university with no previous knowledge of probability theories in order to analyze their intuitive ability to tackle probability problems.